Numerical Simulation of Long-Term Deterioration of Rock Mass Supported by Shotcrete Lining - Kong, Chao; Wang, Haiyan; Zhao, Kai; Gao, Xinqiang (Frontiers in Earth Science, 2022)
The deterioration of rock mass and shotcrete lining has major consequences on the long-term performance of tunnels in the weak rock mass. In this paper, the long-term behavior of rock mass and shotcrete in tunnels was simulated by using the three-dimensional finite difference method, considering the nonlinear deterioration mechanism. The degradation of rock mass was simulated by weakening the mechanical parameters, while the deterioration of shotcrete was modelled by decreasing the thickness. The support pressure, internal force and displacement of secondary lining were monitored with the gradual degradation of rock mass and shotcrete. As a consequence, the factor of safety (FoS) evolution with time was discussed. The results indicated that: (1) The deterioration of both rock mass and shotcrete would significantly increase the rock pressure on the secondary lining, leading to an increase in the displacement (0mm up to 14mm). The FOS of secondary lining was reduced by 85%. (2) The influence of shotcrete’s deterioration on the secondary lining was relatively small, and the rock pressure on the secondary lining increased from 0kPa to 13.8kPa. The long-term safety of tunnel is remarkably affected by the deterioration of rock mass, depending on the deterioration characteristics of rock mass. Therefore, the deterioration characteristics of rock mass should be fully considered in the tunnel maintenance.